#TITLE_ALTERNATIVE# - RIYANTI (10103001), SISKA
In this final project we will discuss about the application of stochastic optimal control theory in finance. The application is determining optimal portfolio for an investor that invest his money on two different assets. The two different assets are risk-free asset and risky asset. The optimal portfolio determined by finding the optimal proportion of money that the investor will invest so that he will get a maximum result. This optimal proportion is the control of the investment portfolio. The model of this investment portfolio has a form as stochastic differential equation (SDE). We will solve this equation so that we can make a simulation to show that the proportion that we get by using stochastic optimal control theory gives a maximum result.